Emission reduction effects of the green energy investment projects of China in belt and road initiative countries. Issue 1 (16th December 2020) - Gu, Alun; Zhou, Xiaoyu
ABSTRACT: Investment and construction of power infrastructure are directly related to the achievement of sustainable development goals. China's trade and investment with BRI (Belt and Road Initiative) countries have maintained growth trend. The development and construction of these investment projects certainly have impacts on the economic development mode and sustainable development goals of the countries. On collecting the basic information of the renewable energy investment projects, this paper compares and calculates the current power technology structure and grid emission factors of the host countries, and analyses the carbon emission level of electricity generation from the perspective of the whole life cycle. Making it as the benchmark, this paper also analyzes the current China's invested wind and solar energy projects and the carbon emission reduction benefits to the host country. The results show that at present, China has about 36 renewable energy investment projects in BRI countries, with an installed capacity of 15.75GW (China as the project owner or investor), and achieve at least 48.69M tCO2 emission reduction. This shows that China's effective investment and implementation of the green projects will provide a strong impetus for the energy transformation and the improvement of their energy security in BRI countries.